Effect of Training Method and Spraying Gibberellic and Salicylic Acide on Some Vegetative Growth Characters of Snapdragon Plants Antirrhinum majus L. - Ali, Yueamar Ahmed; Al-Sheikhli, Abdulrahman Abdulqader (Journal of agricultural, environmental and veterinary sciences, 2019)
The experiment was conducted at research station of the Horticulture and landscape department/ Agriculture college/ Diyala university during 2017 - 2018 seasons (8/10/2017 - 4/5/2018). The objectives of the experiment were to investigate the effect of training method , training method included four types (single stem, double stems , three stems and four stems). Gibberellic acid sprayed with two concentration (100 , 200 mg.L-1) also salicylic acid sprayed with two concentration (50, 100 mg.L-1) and control treatment sprayed two times with distilled water in 15/1/2018 and 15/2/2018.Training methods had significant effects on shoots growth characteristics, Single-stem training method had the best regarding plant height132.36cm, leaves chlorophyll content28.29%, total carbohydrate content58.78Spad unit. Four-stem training method had best results regarding leaves number269.72 leaf/plant, leaf area3235.98cm2/plant, fresh weigh of shoots72.77gm/plant, dry weigh of shoots19.18gm/plant. give spraying 100 mg/l of gibberellic acid had best results regarding plant height124.80cm, leaves number172.91leaf/plant, leaves area2872.81cm2/plant, fresh weight of shoots73.99gm/plant, dry weight of shoots19.48gm/plant, leaves chlorophyll content55.07spad unit, total carbohydrate content28.29%. Interactions between the studied factors had significant effect in all studied characteristics.
Keywords: Snapdragon Plant; Gibberellic; Salicylic; spray leaf's